THE ACCRETION DISK CORONA AND DISK ATMOSPHERE OF 4U 1624-490 AS VIEWED BY THE CHANDRA-HIGH ENERGY TRANSMISSION GRATING SPECTROMETER - Xiang, Jingen; Lee, Julia C.; Nowak, Michael A.; Wilms, Jörn; Schulz, Norbert S. (Astrophysical Journal, 2009)
We present a detailed spectral study ( photoionization modeling and variability) of the "Big Dipper" 4U 1624-490 based on a Chandra-High Energy Transmission Grating Spectrometer ( HETGS) observation over the similar to 76 ks binary orbit of 4U 1624-490. While the continuum spectrum can be modeled using a blackbody plus power law, a slightly better fit is obtained using a single Gamma = 2.25 power-law partially ( 71%) covered by a local absorber of column density N-H, Local = 8.1(-0.6)(+0.7) x 10(22) cm(-2). The data show a possible quasi-sinusoidal modulation with period 43(-9)(+13) ks that might be due to changes in local obscuration. Photoionization modeling with the xstar code and variability studies of the observed strong Fe xxv and Fe XXVI absorption lines point to a two-temperature plasma for their origin: a highly ionized component of ionization parameter xi(hot) approximate to 10(4.3) erg cm s(-1) ( T similar to 3.0 x 10(6) K) associated with an extended accretion disk corona of radius R similar to 3 x 10(10) cm, and a less-ionized more variable component of xi approximate to 10(3.4) erg cm s(-1) ( T similar to 1.0 x 10(6) K) and xi approximate to 10(3.1) erg cm s(-1) ( T similar to 0.9 x 10(6) K) coincident with the accretion disk rim. We use this, with the observed Fe xxv and Fe XXVI absorption line variations ( in wavelength, strength, and width) to construct a viewing geometry that is mapped to changes in plasma conditions over the 4U 1624-490 orbital period.
Keywords: accretion; accretion disks; plasmas; X-rays: binaries; X-rays: individual (4U 1624-490)